A Comparison of Sound Level Monitoring Using Android-Based Smartphone Applications With The Actual Sound Level Meter - Linggam, Eileen Meretha; Ismon, Maznan (Research Progress in Mechanical and Manufacturing Engineering, 2022)
This study compares the performance of the sound level meter applications in the Android smartphone with the actual device and examines the capability of the SLM applications in a smartphone as a replacement of the actual sound level meter. The sound level is tested by a minimum of 5 applications to identify the application that shows the nearest decibel value to an actual device. The sources of sound are generated by dropping a marble onto a steel plate and a sound produced by a car engine. Based on the experiment of dropping marble, the result shows that the SLM application 3 is approximate to the actual device with the difference average decibel value (dB) obtained is 0.5 dB. While for the measuring sound produced by a car engine experiment, the decibel value of SLM application 4 is the nearest to the actual device where the difference of average decibel value with the actual device is 1.1 dB. The study found that there are no smartphone SLM applications that fulfill the IEC or ANSI standards, and they are not ready to replace the professional device as Sound Analyzer (TES-1358). It is preferable to put the smartphone in flight mode when testing the application because it can be used offline to minimize disruptions while obtaining readings. Both the smartphone and the actual SLM should be set on a sturdy tripod with resilient blocks to isolate the device from vibration and the resulting inaccurate readings.